Digital Governance and Digital Divide: A Matrix of the Poor's Vulnerabilities - Rutiana Dwi Wahyunengseh; Sri Hastjarjo; Tri Mulyaningsih; Didik G. Suharto (Indonesian Association for Public Administration, 2020)
Although the internet penetration has reached 64.8% of the population (APJII, 2019), yet the digital divide is still a major issue in Indonesia; especially among the poor. This paper aimed to study and to explain the risks of digital governance implementation in the poverty reduction policies; with the study on how the poor obtains and shares public information in the digital governance era as the focal point. The study was conducted in a city in Indonesia that has been awarded with the Smart City Award. The data was analyzed using descriptive statistics and Social Network Analysis. The study found that some of the poor groups are adapting to the digital governance with the help of the social network in their community; and some of them are alienated digitally. They have been at risk of become marginalized both socially and economically. This paper suggested further studies focusing on the information demand among the poor and the use of new communication technology in the poverty reduction policy making that is inclusive.